Assessment of the Efficiency of Resource Potential Employment by the Communities of lviv Region of Ukraine - Yatsiv, Ihor; Khirivskyi, Roman; Pasichnyk, Tymofii; Petryshyn, Liudmyla; Kucher, Lesia (European Journal of Sustainable Development, 2019)
The article supplies assessment of the efficiency of resource potential employment by some communities in Lviv region. The work studies the main sources of the resources of amalgamated territorial communities and makes grouping of them according to the criteria of their essence and importance in the strategy of development of the community’s resource potential. The research analyzes financial capability of the communities, considers the recent results, obtained by Ukrainian scientists concerning the resource potential of amalgamated territorial communities. The authors of the work applied the methods of standard coefficients to transfer the indices of quantity into quality analogues. The indices were used to make rating of amalgamated territorial communities, to depict different factorial and resultant aspects of the resource potential of amalgamated territorial communities and assess them. Applyng the method of standard coefficients and matrix of the Boston Consulting Group, the work determines position of each community referring to density of population and resource of the capacity for work of amalgamated territorial communities. It also calculates rating indices for comparison of public formations in social sphere, and estimates expenditures for administrative personnel of each community. The proposed methods enable keeping track with not only dynamics of the rating assessment of communities, but also priority of the factorial indices concerning improvement and development of the communities. Those methods can be used not just referring to rural, but also to urban formations, based on a uniform measuring for all peculiarities. It helps to move from subjectivism and inconvenient use of expert assessments and weighting coefficients while completing the uniform integrated indices. Keywords: territorial community; social development; resource support; administrative and territorial reform; method of standard coefficients; matrix of the Boston Consulting Group.